A continuum of governance regimes: A new perspective on co-management in irrigation systems. Issue 66 (December 2016) - Frey, Ulrich J.; Villamayor-Tomas, Sergio; Theesfeld, Insa
Highlights: A new classification for state-, community- and co-managed irrigation systems is proposed. Co-management is operationalized in a detailed way. Distinction of co-management patterns can be expressed along a continuum. Performance of a large number of irrigation systems (n = 244) is measured across several dimensions. Successful community-based management is not confined to small irrigation systems.